A meta-analysis of the effects of plyometric training on muscle strength and power in martial arts athletes - Yuan, Q.; Deng, N.; Soh, K. G. (BMC Sports Science, Medicine and Rehabilitation, 2025)
Background Plyometric training (PT) was explored as an effective intervention for enhancing muscle strength and power. However, its specific impact on these attributes in martial arts athletes had not been systematically evaluated. Therefore, the objective of this meta-analysis was to provide a quantitative assessment of the impact of PT on muscle strength and power in martial arts athletes. Additionally, it aimed to investigate potential moderators that could influence this relationship.